Assessment in the Crosshairs: How Contextual Factors Shape English Teachers' Conceptions of Assessment - Prastikawati , Entika Fani; Curle, Samantha; Vivekanantharasa, Raveenthiran (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study explores English teachers’ conceptions of assessment and the influence of contextual factors operating at the classroom levels within the Indonesian secondary education system. A representative survey was conducted among 236 English teachers from public and private secondary schools across Central Java, Indonesia. The findings reveal that teachers predominantly endorse assessment for purposes of student improvement, student accountability, and school accountability, while comparatively fewer teachers view assessment as irrelevant. Although many respondents express confidence in their assessment knowledge and perceived competence, concerns persist regarding the degree of professional trust they receive particularly in relation to assessment decision-making at both school and policy levels. To further explore underlying patterns, a latent class analysis (LCA) was conducted based on English teachers' responses to the “assessment as irrelevant” dimension. The analysis identified distinct groups of teachers, with those expressing higher levels of assessment irrelevance found across all schools and subject areas. These teachers tended to report lower confidence in assessment preparation, perceived less support from their institutions, and placed reduced value on academic achievement within societal contexts. The results underscore the complexity of teacher belief systems and the interplay of contextual forces shaping conceptions of assessment in Indonesia. Implications are discussed for assessment policy, school leadership, and professional development aimed at strengthening assessment literacy among English language teachers.